Pengembangan Sumber Belajar Majalah Pembelajaran Biologi Berbasis Eksplorasi Tumbuhan Obat Masyarakat Desa Kalibaru Kulon Banyuwangi - Angga Dwi Nursandi; Agus Prasetyo Utomo; Aulya Nanda Prafitasari (Journal of Natural Sciences, 2023)
Learning resources are the most important component in improving the quality of student learning outcomes.Â  In the learning process, teachers rarely use magazines as a learning resource, so concepts are difficult for students to understand. Magazines are a learning resource that is used tofoster students' interest in lessons and help their understanding of complex and clear material. The purpose of this study is to developÂ  a valid biology learning magazine based on the exploration of medicinal plants of Kalibaru Kulon Village, Kalibaru District, Banyuwangi Regency. The method in this study is the development method (Research and Development) using the ADDIE model. The resulting product will be validated by validators to determine the level of validity of the magazine developed. The results of developing the magazine's learning resources meet the average criterion of 90% which states that the biology learning magazine meets the criteria of "Very Decent, Does Not Need to Be Revised".